The Impact of Covid-19 on the Shanghai Stock Exchange - Ridha Ben Saleh (Journal of Pure & Applied Sciences, 2020)
This study aims to measure the impact of Covid-19 on the Shanghai Stock Exchange in the Republic of China, during the first third of 2020. To do so, simple regression analysis was applied by using ordinary least square (OLS) method. Results of the study revealed that Covid-19 has affected the Shanghai Stock Exchange negatively. In other words, the rise of covid-19 in China by one thousand confirmed cases daily, this leads to a decrease in the Shanghai Stock Exchange by more than 0.1 percent. Also, results showed that the Corona pandemic was contained in the republic of China. Therefore, this study provides important information to investors, first, to keep investing in Shanghai Stock Exchange because the pandemic was brought under control inside and widely spread elsewhere. Second, to scale up the weight of shares of health and technology companies and to reduce airlines and tourism shares weight in the financial portfolios.